Perovskites under extreme conditions: pushing the limits of neutron diffraction - Capone, Mara (The University of Edinburgh, 2020)
The application of hydrostatic pressure and temperature are effective methods for manipulating and correlating crystal structures and physical properties of materials. Volume, interatomic distances, chemical bonds, local atomic coordination are all strongly altered by pressure and temperature, which can either distort or symmetrise the structure and cause the alteration of the crystal symmetry with huge consequences on the physical properties. High Pressure (HP), in particular, can induce significant structural and physical changes and can be used to explore structural-property relationships in a huge variety of materials. Perovskite compounds are excellent candidates for HP investigations owing to remarkable changes in their structural, electrical and magnetic properties in response to a variation of the chemical composition x or volume of the material. Diverse crystal structures and physical properties are found in the perovskite family, which can be controlled by the application of pressure and/or temperature. Among the broad spectrum of experimental techniques, neutron-powder diffraction offers several advantages for in situ investigation under extreme conditions of perovskite materials. Neutron diffraction provides the ability to map the relative positions of atoms and their structural changes down to the nanometre length-scale. The complex dependence of the coherent neutron scattering cross section on the atomic number Z of the scattered material enables diffraction comparison between neighbouring elements in the periodic table and isotopes, and a higher sensitivity to light elements such as hydrogen or oxygen in the presence of heavier atoms. The primary aim of this thesis investigates perovskite oxides and focuses on their structural and physical characterisation under the application of hydrostatic pressure and/or temperature. Perovskites exhibit physical properties utilised in several technological fields, from the magnetoresistence of lanthanum manganites, to the catalytic activity of cobalt-based compounds or to the antiferromagnetism of lanthanum ferrite materials. This thesis reports a pressure and temperature-dependent neutron-diffraction study of the lanthanum cobaltite LaCoO3. The present study gives insight into the unique pressure and temperature-dependent electronic properties of LaCoO3 and aims to deepen the understanding of structural-electronic correlations in this material. Neutron-diffraction data were collected at 120, 290 and 480 K in the 0-6 GPa pressure range and used to report the equation of state of the sample at each temperature and to accurately determine chemical bonds and structural parameters. A similar investigation reports details of the structural and physical properties of the lanthanum ferrite LaFeO3 material. Neutron-diffraction data were collected at 110 and 290 K in the 0-6.5 GPa and 0-16.2 GPa ranges, respectively. This work analyses the equation of state of the sample and changes within its structure under extreme conditions. This study also monitors the magnetic behaviour of LaFeO3 and how its magnetic moment varies under the application of hydrostatic pressure. In addition, high-pressure Raman spectroscopy data were collected at 290 K in the 0-7.6 GPa pressure range, and the structural-spectroscopic relationships of LaFeO3 analysed. Chemical doping is a further strategy to alter the structure of materials and tune their physical properties. Specific doping elements are used to produce subtle distortions in crystal structures and to regulate changes in their physical properties. This thesis describes the effect of selective doping on the LaCoO3 oxide, which is the parent compound of several material series of the type La(Co,B)O3 (where B is a different transition-metal ion). High-pressure neutron-diffraction experiments were performed in the 0-6 GPa range at 290 K on the LaCo0.9Mn0.1O3 material. This study analyses the effect of the low manganese doping on the crystal structure of LaCoO3 and reports changes in the equation of state, structural parameters and chemical bonds. The introduction of manganese ions also in influences the magnetic properties of this material. DC magnetometry measurements were performed on LaCo0.9Mn0.1O3 in the 0-4 GPa pressure range and used to determine the Curie temperature of the sample, which shows a strong dependence not only on the chemical doping, but also on the applied pressure. The aforementioned high-pressure neutron-diffraction experiments were performed on the PEARL diffractometer, the instrument dedicated to performing high-pressure diffraction measurements at the ISIS Neutron and Muon Source. The PEARL instrument has been running for nearly three decades and diverse pressure tools are used to carry out high-pressure experiments and different sample environments have been developed in the past. Another important part of the work presented in this thesis focuses on extending the pressure range, which can currently be applied as part of the user programme on the ISIS diffractometer, by the development of new pressure cells for neutron diffraction, such as diamond anvil cells (DACs). DACs have been designed and developed for the PEARL instrument and their integration has already started. These new pressure cells will provide the ability to remarkably reduce the sample volume during experiments, hence resulting in an increased accessible pressure range.
Keywords: high pressure; neutron diffraction; Perovskite; diamond anvil cell